(untitled) (Development Service Industry Management, 2025)
The study examines approaches to forming an adaptive, scenario-oriented strategy for the foreign economic activity (FEA) of Ukraine’s agrarian sector under conditions of global turbulence. The relevance stems from the high uncertainty of the environment (security risks, logistics bottlenecks, regulatory changes in the EU, and the requirements of the Green Deal), which necessitates a shift to scenario-based management. Methodologically, PESTLE and SWOT analyses are integrated to build a factor profile and to identify strengths/weaknesses and opportunities/threats at both enterprise and sector levels. On this basis, three alternative development scenarios (optimistic, baseline, pessimistic) are constructed with parameterization of key drivers: political stability (P), logistics cost (C), market access (R), technological adoption (T), human capacity (S), and legal compliance (L). The quantitative core is an economic-mathematical specification of expected agri-food export volumes as a linear function of these factors with an inverse dependence on logistics costs (1/C); sensitivity analysis is applied to rank effects and verify the robustness of decisions. The results indicate the dominance of security/logistics variables (P and C), while R, T, and L ensure a gradual build-up of export potential through expanded market access, productivity gains, and compliance with EU requirements; S has a moderate yet statistically significant effect. A scenario-action matrix is formulated covering the diversification of sales channels, modernization and digitalization of logistics and traceability, development of processing, risk-hedging instruments, and strengthening of compliance. Limitations relate to data quality and the exogeneity of security shocks; further research will include estimating the model on enterprise panel data, robustness checks, and microsimulations of changes in logistics tariffs and insurance.